2009
DOI: 10.7557/23.6012
|View full text |Cite
|
Sign up to set email alerts
|

Ten years later

Abstract: How does the participation in Massively Multiplayer Online Role-Playing Games (MMORPGs) affect the individual gamer’s self- development and social integration? The results of 1998/99’s empirical study dealing with the topic of “Integrative Potentials of New Technologies” (see Götzenbrucker 2001) already highlighted the fact that differing gaming environments attracted specific types of gamers. These various types of gamers were characterized by different kinds of lifestyles and divergent social positions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…However, high-powered studies seem to imply that many such health problems are cyclical and do not continue for 12 months, which is the time suggested for a gaming disorder diagnosis to be assigned by the WHO (e.g., Strittmatter et al 2016;Thege et al 2015;Weinstein et al 2017). Although other longitudinal findings likewise indicate gaming to be an evolving activity in people's lives (e.g., Götzenbrucker & Köhl 2009;Karlsen 2013;Karhulahti 2020), such changes often take longer than 12 months to surface. Therefore, we set the following qualitative hypothesis.…”
Section: Programmatic Registered Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high-powered studies seem to imply that many such health problems are cyclical and do not continue for 12 months, which is the time suggested for a gaming disorder diagnosis to be assigned by the WHO (e.g., Strittmatter et al 2016;Thege et al 2015;Weinstein et al 2017). Although other longitudinal findings likewise indicate gaming to be an evolving activity in people's lives (e.g., Götzenbrucker & Köhl 2009;Karlsen 2013;Karhulahti 2020), such changes often take longer than 12 months to surface. Therefore, we set the following qualitative hypothesis.…”
Section: Programmatic Registered Reportmentioning
confidence: 99%
“…They had become attached to gaming early on and kept holding on to it. Because we applied purposive sampling to reach actively gaming players, our data do not describe those who have stopped or reduced playing after successful coping, but previous research evidences this pathway to across countries as well (e.g., Götzenbrucker & Köhl, 2009;Quandt et al 2009).…”
Section: Successful Coping-gamingmentioning
confidence: 99%
“…Fullerton [19] used personality traits to generate a number of gamer types: Competitors (perfectionists), explorers (adventurous), collectors (arrangers), achievers (successbased), jokers (fun), artists (design and creativity), directors (guiders), storytellers (creating worlds) and performers (presenters). Götzenbrucker and Köhl's [21] longitudinal study analyzed the effects of lifestyles, habits and media on game behavior and found that significant defining moments in the player's lives (e.g., new employment) would decrease the duration of their gameplaying. Xu et al [77] examined gamer motivation (what the player thinks about the game), behavior (what the player does during the game) and effect (the social impact of the player on the rest of the player group).…”
Section: Gamer Typologiesmentioning
confidence: 99%